PENYULUHAN HUKUM DALAM UPAYA PENINGKATAN KESADARAN HUKUM BERLALULINTAS MELALUI PEMAHAMAN TERHADAP ISI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Nanci Yosepin Simbolon; Mhd. Ansori Lubis; Alusianto Hamonangan; Lestari Victoria Sinaga (Jurnal Abdimas Bina Bangsa, 2023)
The development of science and technology in the field of transportation has an impact on human life, where currently the use of motorized vehicles is increasing rapidly in supporting various community activities. In addition to providing benefits, an increase in the number of motorized vehicles on the highway can cause traffic jams and is also directly proportional to the increase in the number of traffic violations that occur on the highway which can be one of the causes of traffic accidents, where traffic violations occur due to lack of knowledge and understanding of the law that causes low awareness and compliance with public law in traffic on the highway. For this reason, it is important to carry out community service activities in the form of legal counseling regarding the culture of orderly traffic on the highway according to Law Number 22 of 2009 concerning Road Traffic and Transportation, so as to provide legal knowledge and understanding to the public and then will raise awareness and legal compliance with traffic regulations on the highway. The research method used is a normative juridical approach, descriptive analytical research specifications. The research phase was carried out through a literature study to examine primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques were carried out through document studies, and data analysis methods were carried out through normative qualitative. The results of the study show that understanding the contents of Law No. 22 of 2009 concerning Road Traffic and Transportation is difficult to measure the level of legal awareness of citizens because there are other influencing factors, namely the role model of officials and oversight mechanisms also determine it